2022
DOI: 10.1155/2022/3190370
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Related Factors of Mother-to-Child Transmission of AIDS and Evaluation of Measures to Prevent Mother-to-Child Transmission

Abstract: AIDS is still a major public health facing the world. With the implementation of AIDS prevention projects and the continuous maturity of technology, more and more HIV-positive women choose to have children. However, the children born to these women are a special group. Exposure to HIV and antiviral drugs during the fetal period can increase the success rate of children’s elimination of the mother, which is worthy of attention and research. This article focuses on the analysis of the related factors of mother-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Sometimes, the infected person may not show the symptoms but can infect healthy individuals 4 . Another direct spread of infectious diseases occurs from mothers to their children either through the placenta for the unborn child or through breast milk 5 . The indirect transmission of infectious diseases occurs if the microorganism remains on physical objects such as doorknobs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, the infected person may not show the symptoms but can infect healthy individuals 4 . Another direct spread of infectious diseases occurs from mothers to their children either through the placenta for the unborn child or through breast milk 5 . The indirect transmission of infectious diseases occurs if the microorganism remains on physical objects such as doorknobs.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Another direct spread of infectious diseases occurs from mothers to their children either through the placenta for the unborn child or through breast milk. 5 The indirect transmission of infectious diseases occurs if the microorganism remains on physical objects such as doorknobs. When an infected person touches the object, they left germs that in contact with the healthy person can cause infection.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of PMTCT interventions is estimated to result in a 15%-45% chance of mothers transmitting HIV to their children when pregnant, during delivery and while breastfeeding (Gebre et al, 2021). It is further estimated that a quarter of HIV HIV-exposed infants (HEI) get infected during delivery, whereas a fifth is likely to be infected during pregnancy and breastfeeding periods (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%